2021
DOI: 10.1210/endocr/bqab082
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Neuroendocrinology: Emerging Role for Neurohypophyseal Hormones in Pathophysiology

Abstract: Arginine vasopressin (AVP) and oxytocin (OXY) are released by magnocellular neurosecretory cells that project to the posterior pituitary. While AVP and OXY currently receive more attention for their contributions to affiliative behavior, this mini-review discusses their roles in cardiovascular function broadly defined to include indirect effects that influence cardiovascular function. The traditional view is that neither AVP nor OXY contributes to basal cardiovascular function, although some recent studies sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 183 publications
0
0
0
1
Order By: Relevance
“…46 This hormone is produced by magnocellular neurosecretory cells located in the supraoptic and PVN (which house oxytocin-producing neurons). 47 a-sHyp, which encompasses the PVN, exhibits notable volume loss in ALS, 22,23 as shown in our study. These findings support the presence of distinct neuropeptide expression abnormalities that could potentially contribute to the pathogenesis of specific cognitive and behavioral symptoms within the spectrum of this disease.…”
Section: The Involvement Of Hypothalamic Nucleisupporting
confidence: 82%
See 1 more Smart Citation
“…46 This hormone is produced by magnocellular neurosecretory cells located in the supraoptic and PVN (which house oxytocin-producing neurons). 47 a-sHyp, which encompasses the PVN, exhibits notable volume loss in ALS, 22,23 as shown in our study. These findings support the presence of distinct neuropeptide expression abnormalities that could potentially contribute to the pathogenesis of specific cognitive and behavioral symptoms within the spectrum of this disease.…”
Section: The Involvement Of Hypothalamic Nucleisupporting
confidence: 82%
“…Oxytocin (OXT) is a neuropeptide that plays an important role in the regulation of social cognition and emotional behaviors such as anxiety and depression 46 . This hormone is produced by magnocellular neurosecretory cells located in the supraoptic and PVN (which house oxytocin‐producing neurons) 47 . a‐sHyp, which encompasses the PVN, exhibits notable volume loss in ALS, 22,23 as shown in our study.…”
Section: Discussionsupporting
confidence: 62%
“…Expression of vasopressin gene is influenced by changes of body fluid osmolality and blood volume, as well as by constituents of the hypothalamo-hypophysial-adrenal axis, pain, cytokines and inflammation factors, especially those associated with COVID-19 [116,[121][122][123][124][125]. Vasopressin gene expression and AVP mRNA abundance are enhanced by chronic osmotic simulation and are decreased in hypoosmolality.…”
Section: Genomic and Non-genomic Effects Of Vasopressinmentioning
confidence: 99%
“…It has been reported that the plasma levels of vasopressin are elevated during the development of heart failure [251][252][253]. While the activation of the V 1a receptors via vasopressin results in the development of vasoconstriction, hypertension, cardiac hypertrophy and heart failure, the activation of the V 2 receptors is associated with fluid retention, leading to the development of volume overload, venous congestion, edema and lung congestion [254][255][256][257][258][259]. Vasopressin not only causes water retention but also results in kidney dysfunction in heart failure patients.…”
Section: Role Of Vasopressin In Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%